Increase in Serum Soluble Tim-3 Level Is Related to the Progression of Diseases After Hepatitis Virus Infection - Chen, Lingli; Yu, Xiaomei; Lv, Chunyan; Dai, Yaping; Wang, Tao; Zheng, Shaoxiong; Qin, Yuan; Zhou, Xiumei; Wang, Yigang; Pei, Hao; Fang, Hongming; Huang, Biao (Frontiers in Medicine, 2022)
Background: Hepatitis virus infection is a widespread and serious infectious disease, and most patients with liver cirrhosis and hepatocellular carcinoma are accompanied by viral infections. T cell immunoglobulin and mucin domain molecule 3 (Tim-3) is an immune checkpoint molecule that negatively regulates T cell responses, playing an extremely important role in infectious diseases. However, reports about the role of soluble Tim-3 in serum in hepatitis virus infection are few. Therefore, this study explored changes in serum soluble Tim-3 (sTim-3) levels in patients infected with hepatitis B virus (HBV), hepatitis C virus (HCV), or hepatitis E virus (HEV). Methods: This study applied high-sensitivity time-resolved fluorescence immunoassay for the detection of serum sTim-3 levels. A total of 205 cases of viral hepatitis infection (68 cases of HBV infection, 60 cases of HCV infection, and 77 cases of HEV virus infection) and 88 healthy controls were quantitatively determined. The relationship between serum sTim-3 levels and disease progression after hepatitis virus infection was analyzed. Results: Patients with HBV infection (17.36 ± 11.43 ng/mL), HCV infection (20.62 ± 14.89 ng/mL), or HEV infection (24.83 ± 18.41 ng/mL) had significantly higher serum sTim-3 levels than the healthy control group (8.33 ± 3.51 ng/mL, P < 0.0001). Patients with hepatitis and fibrosis infected with HBV (24.92±15.20 ng/mL), HCV (33.57 ± 20.01 ng/mL), and HEV (31.03 ± 19.17 ng/mL) had significantly higher serum sTim-3 levels than patients with hepatitis but without fibrosis (13.30 ± 5.55, 17.04 ± 7.90, and 21.48 ± 17.2 6 ng/mL; P < 0.05). Conclusion: Serum sTim-3 level was elevated in patients infected with HBV, HCV, or HEV and gradually increased in patients with hepatitis or hepatitis with hepatic fibrosis. It has a certain role in the evaluation of the course of a disease after hepatitis virus infection.